2018
DOI: 10.7326/m17-1907
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Analgesic Use and Risk for Invasive Pneumococcal Diseases

Abstract: National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 36 publications
4
48
1
1
Order By: Relevance
“…Importantly, each of these studies consistently reported that patients using long-acting and high potency opioid formulations, opioids at high doses and opioids previously described as exhibiting immunosuppressive properties (i.e., morphine, codeine, fentanyl and methadone) had the highest risk for infection. The studies also noted a high risk for infections among patients recently initiating opioid use [18][19][20].…”
Section: Supporting Evidence From Recent Studies Among Humansmentioning
confidence: 95%
See 3 more Smart Citations
“…Importantly, each of these studies consistently reported that patients using long-acting and high potency opioid formulations, opioids at high doses and opioids previously described as exhibiting immunosuppressive properties (i.e., morphine, codeine, fentanyl and methadone) had the highest risk for infection. The studies also noted a high risk for infections among patients recently initiating opioid use [18][19][20].…”
Section: Supporting Evidence From Recent Studies Among Humansmentioning
confidence: 95%
“…Opioid use was associated with an increased risk of multiple infection types across the three studies, demonstrating that the association cannot be fully explained by other opioid-related mechanisms which could contribute to infection (i.e., opioid-induced respiratory depression and microaspiration leading to pneumonia) [18][19][20]. Furthermore, each study applied strategies to account for potential protopathic bias (i.e., the possibility that individuals initiated opioid use to treat early symptoms of infection) and confounding by indication (i.e., individuals received opioids for an indication that is a risk factor for infection itself ) [18][19][20].…”
Section: Supporting Evidence From Recent Studies Among Humansmentioning
confidence: 97%
See 2 more Smart Citations
“…A growing concern is related to the use of these compounds in humans as, like in animals, opioid use is associated with an increased risk of bacterial infections like pneumococcal diseases [50]. A better understanding of how endogenous opioids as well as synthetic ones interact with bacterial cells may help in the identification of potential bacterial targets and the development of dual-therapy in high-risk patients.…”
Section: Effects Of Peptidic Hormones On Gram-negative Bacteriamentioning
confidence: 99%